2017
DOI: 10.1128/jvi.02201-16
|View full text |Cite
|
Sign up to set email alerts
|

Lineage A Betacoronavirus NS2 Proteins and the Homologous Torovirus Berne pp1a Carboxy-Terminal Domain Are Phosphodiesterases That Antagonize Activation of RNase L

Abstract: Viruses in the family Coronaviridae, within the order Nidovirales, are etiologic agents of a range of human and animal diseases, including both mild and severe respiratory diseases in humans. These viruses encode conserved replicase and structural proteins as well as more diverse accessory proteins, encoded in the 3= ends of their genomes, that often act as host cell antagonists. We previously showed that 2=,5=-phosphodiesterases (2=,5=-PDEs) encoded by the prototypical Betacoronavirus, mouse hepatitis virus (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 30 publications
3
31
0
Order By: Relevance
“…We previously reported that MERS-CoV NS4b is a member of the 2H-phosphoesterase superfamily of proteins and antagonizes OAS-RNase L activation during MERS-CoV infection through its 2′,5′-PDE activity (19, 29). Unlike previously studied viral PDEs such as mouse hepatitis virus (MHV) NS2, the torovirus pp1a C-terminal domain, and the rotavirus VP3 C-terminal domain, which exhibit primarily cytoplasmic localization (23, 24), NS4b localizes primarily to the nucleus (Fig. 2B), suggesting additional functions.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…We previously reported that MERS-CoV NS4b is a member of the 2H-phosphoesterase superfamily of proteins and antagonizes OAS-RNase L activation during MERS-CoV infection through its 2′,5′-PDE activity (19, 29). Unlike previously studied viral PDEs such as mouse hepatitis virus (MHV) NS2, the torovirus pp1a C-terminal domain, and the rotavirus VP3 C-terminal domain, which exhibit primarily cytoplasmic localization (23, 24), NS4b localizes primarily to the nucleus (Fig. 2B), suggesting additional functions.…”
Section: Resultsmentioning
confidence: 69%
“…Our studies of NS4b reveal that in addition to antagonizing OAS-RNase L and preventing NF-κB activation, NS4b antagonizes IFNL1 expression, with this function dependent on both its catalytic activity and nuclear localization and independent of its interaction with the OAS-RNase L pathway. This is a unique role for virus-encoded phosphodiesterases, which otherwise lack an NLS and act solely as OAS-RNase L antagonists (12, 2326). Together, the results demonstrate that NS4a and NS4b mediate both expected and unexpected functions during MERS-CoV infection and further demonstrate the importance of studying the function of these proteins in the context of infection to uncover the full range of their interactions with the innate immune response.…”
Section: Introductionmentioning
confidence: 99%
“…Many viruses have evolved specific mechanisms and in some cases specific proteins (coronaviruses, rotaviruses, and Theiler's virus) to evade the antiviral effects of RNase L (35)(36)(37)(38)(39), which we suggest is at least in part because RNase L can be activated even while IFN signaling is antagonized (Fig. 2B) (40).…”
Section: Figmentioning
confidence: 80%
“…The binding of 2-5A drives RNase L self-assembly into catalytically active homodimers and high-order oligomers that cleave single-stranded RNA (ssRNA), but not dsRNA molecules inside cells, and exhibit sequence specificity for UN^N sites (m arks the cleavage site; N = A, G, U or C [Han et al 2012[Han et al , 2014Huang et al 2014]). As an arm in the IFN response, RNase L mediates innate immune defense against viruses (Ireland et al 2009;Goldstein et al 2016) and bacteria (Li et al 2008). The functions of RNase L span beyond infection control.…”
Section: Introductionmentioning
confidence: 99%